Information for Decision Making: Readings in Cost and Managerial Accounting (Book). - Meyer, Philip E.; Sorensen, James E. (The Accounting Review, 1983)
Reviews the book "Information for Decision Making: Readings in Cost and Managerial Accounting," edited by Alfred Rappaport.